From capital to commons : exploring the promise of a world beyond capitalism - Gerhardt, Hannes (Alternatives to capitalism in the 21st century, 2023)
In this stimulating analysis, Hannes Gerhardt outlines the potentials and challenges of a technology-enabled, commons-focused transition out of capitalism. The book shows that openness and cooperation are more beneficial in today's economies and societies than competition and profit-seeking. Driven by this conviction, Gerhardt identifies key imperatives for overcoming capitalism, from democratizing our digital, material, and financial economies to maintaining a robust, political mobilization. Using clear examples, he explores tactical openings through the lens of 'compeerism', a newly constructed framework that highlights the latent counter-capitalist possibilities, but also limits, of our emerging technological landscape. This is an accessible contribution to counter-capitalist discourse that is both inspiring and pragmatic for academics and activists alike.